Phage therapy in the inactivation of Pseudomonas syringae pv. actinidiae in kiwifruit plants - Pinheiro, Larindja Amanda Monteiro (2021)
Pseudomonas syringae (P. syringae) is the causative agent of diseases in a wide variety of plants and includes more than 60 pathovars. Pseudomonas syringae pv. actinidiae (Psa) is one of the pathovars of this species and the causative agent of bacterial cancer in kiwifruit plants. Psa is responsible to high economic losses, seriously affecting the global production of kiwifruit in many countries, including Portugal. The most common treatments for biocontrol of Psa and other infections caused by Pseudomonas syringae pathovars in plants involve copper derivatives and /or antibiotics. However, these treatments should be avoided due to both their high toxicity and development of bacterial resistance. One promising alternative to conventional treatments is the use of phage therapy to control Psa infections in plants. Phages are bacterial viruses and their antibacterial nature through induction of bacterial lysis, their high host specificity and rapid reproduction enable them to control bacterial populations. The use of phages to control bacterial infections has been reported across numerous fields by many researchers. However, there is no report regarding the use of phages to eliminate Psa in kiwifruit plants. Thus, the objective of this work was to evaluate the efficacy of phage therapy to inactivate or reduce Psa in kiwifruit plants. Phage Ф6 (a commercially available and safe phage) was characterized in order to evaluate its potential application in the control of diseases caused by P. syringae, namely caused by Psa. Initially, phage 6 was characterized in terms of host range, latent period, burst size, adsorption to the host and development phage-resistant mutants using its natural host P. syringae pv. syringae. As the kiwifruit plants are exposed to the natural variability of environmental factors, the influence of pH, temperature, solar radiation and UV radiation on phage 6 viability was also evaluated. First, the phage-bacteria interaction was characterized in vitro, using liquid culture medium at MOI of 1 and 100. The results revealed that the phage exhibited a broad lytic spectrum against the tested bacteria, infecting, besides the host P. syringae, the Psa strains CRA-FRU 12.54 and CRA-FRU 14.10. The phage at MOI 1 and 100, can be an effective alternative to control the species P. syringae. However, the MOI of 1 (maximum reduction of 3.9 log CFU/mL) was more effective than MOI of 100 (maximum reduction of 2.6 log CFU/mL). The viability of phage  6 in PBS was primarily affected by UV-B radiation exposure (decrease of 7.3 log PFU/mL after 8 h), solar radiation exposure (decrease of 2.1 PFU/mL after 6 h) and high temperatures (decrease of 8.5 PFU/mL after 6 days at 37 °C). The viability of the phage was not significantly affected by conditions as lower temperatures (decrease 2.0 log PFU/mL after 67 days at 15 °C and 25 °C) and pH (decrease 2.3 log PFU/mL at pH 7 and 7.5 and 2.7 log PFU/mL at pH 6.5). Second, to confirm if this phage can be used to control the Psa strains CRA-FRU 12.54 and CRA-FRU 14.10, in vitro, using liquid culture medium, and ex vivo experiments, using artificially contaminated kiwifruit leaves, were done. In the in vitro assays, a reduction of approximately 2.0 log CFU/mL of both Psa strains was observed after 24 h of incubation. In the ex vivo tests, the decrease was lower after 24 h of incubation, 1.1 log CFU/mL of reduction for Psa CRA-FRU 12.54 and 1.8 log CFU/mL of reduction for Psa CRA-FRU 14.10. Overall, phage therapy showed to be an effective and safe method to inactivate the Psa in kiwifruit plants. In order to exploit the full potential of this therapy, further studies are needed, namely field studies in kiwifruit orchards, applying the phages at the end of the day or during night period in order to avoid phage inactivation by UV radiation and high temperature